2016
DOI: 10.1097/meg.0000000000000624
|View full text |Cite
|
Sign up to set email alerts
|

Elevated liver enzymes in inflammatory bowel disease: the role and safety of infliximab

Abstract: Elevated liver enzymes are frequently found in IBD patients and they usually resolve spontaneously. The use of immunomodulators was independently associated with increased ALT. Infliximab is relatively safe in terms of liver impairment and discontinuation of treatment is rarely required in the setting of modest elevations of ALT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 32 publications
2
17
1
Order By: Relevance
“…Authors did not give details on IBD treatment and the most commonly observed pattern of injury was mild cholestasis. Parisi et al[13] report abnormal ALT in 39.2% and grade 2 increase in 7.9% of 176 patients treated with infliximab. In this study, authors identified several risk factors for liver injury: previous abnormal ALT suggesting a preexisting liver disease, immunomodulatory use and duration of infliximab therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Authors did not give details on IBD treatment and the most commonly observed pattern of injury was mild cholestasis. Parisi et al[13] report abnormal ALT in 39.2% and grade 2 increase in 7.9% of 176 patients treated with infliximab. In this study, authors identified several risk factors for liver injury: previous abnormal ALT suggesting a preexisting liver disease, immunomodulatory use and duration of infliximab therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our results appear consistent with previous reports showing ALT elevations in roughly the same proportion of cases. It appears, that transient liver injury occurs during induction, but also during maintenance therapy with a thiopurine as well as anti-TNF[13-15]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anti-TNF α agents, primarily Infliximab, have also been reported to cause drug induced liver injury [18]. However, most of these cases only had mild elevation of liver enzymes, occurring months after initiation of the anti-TNF α agent [18, 19]. Our patient on the other hand had dramatic elevations in her liver enzymes.…”
Section: Discussionmentioning
confidence: 83%
“…The most common form of liver injury related to TNF‐α inhibitors has been shown to be hepatocellular injury with autoantibodies, mostly with positive ANA and some with anti‐smooth muscle antibody, and histologic features consistent with AIH. Development of this pattern of injury has been reported in up to 92% of TNF‐α inhibitor‐induced DILI . Additionally, there seems to be a lack of cross‐reactivity between TNF‐α inhibitors, possibly due to the difference in molecular structure of these agents.…”
Section: Tumor Necrosis Factor Alpha Inhibitorsmentioning
confidence: 99%